2018
DOI: 10.1002/bies.201800165
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Cycle‐Dependent Regulation of Cell Adhesions: Adhering to the Schedule

Abstract: Focal adhesions disassemble during mitosis, but surprisingly little is known about how these structures respond to other phases of the cell cycle. Three recent papers reveal unexpected results as they examine adhesions through the cell cycle. A biphasic response is detected where focal adhesions grow during S phase before disassembly begins early in G2. In M phase, activated integrins at the tips of retraction fibers anchor mitotic cells, but these adhesions lack the defining components of focal adhesions, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Importantly, in mitosis, canonical adhesion complexes are disassembled while adhesive structures resembling plaques are maintained to preserve the interaction with the [60] MTBD-2: Du et al [59] LipidBD-1: Kotak et al [63] LipidBD-2: Zheng et al [64] dyneinBD: Kotak et al [50] LGNBD: Pirovano et al [62] 4.1BD: Kiyomitsu & Cheeseman [66] GoLoco: Du & Macara [51] TPR: Du & Macara [51] DLG-BD: Saadaoui et al [ royalsocietypublishing.org/journal/rsob Open Biol. 10: 190314 substrate needed to achieve effective mitosis, daughter cell respreading and mitotic spindle orientation [19,[96][97][98][99] (see also §4.2 and 4.3).…”
Section: Endocytic Regulation Of Pm Remodelling and Mechanical Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in mitosis, canonical adhesion complexes are disassembled while adhesive structures resembling plaques are maintained to preserve the interaction with the [60] MTBD-2: Du et al [59] LipidBD-1: Kotak et al [63] LipidBD-2: Zheng et al [64] dyneinBD: Kotak et al [50] LGNBD: Pirovano et al [62] 4.1BD: Kiyomitsu & Cheeseman [66] GoLoco: Du & Macara [51] TPR: Du & Macara [51] DLG-BD: Saadaoui et al [ royalsocietypublishing.org/journal/rsob Open Biol. 10: 190314 substrate needed to achieve effective mitosis, daughter cell respreading and mitotic spindle orientation [19,[96][97][98][99] (see also §4.2 and 4.3).…”
Section: Endocytic Regulation Of Pm Remodelling and Mechanical Forcesmentioning
confidence: 99%
“…Not only is the regulation of cell-cell junctions critical to preserve tissue integrity during epithelial cell division, but also the adhesion of mitotic cells to the extracellular matrix plays a crucial role in this process [22,234,237]. As discussed in §2.2, canonical cell-matrix adhesion complexes are disassembled during mitosis, while mitosis-specific adhesion sites are maintained, providing positional memory to mitotic cells and allowing mitotic-spindle orientation, daughter cell separation and re-spreading (figure 5a,b) [96,97]. These structures have been described by different laboratories to be present in several cellular contexts and to display distinct features [19,96,98].…”
Section: Interaction Of Mitotic Cells With the Extracellular Matrix: mentioning
confidence: 99%
“…When considering the balance of the canonical AC–RA/plaque axis, an intriguing case is that of mitosis, where canonical ACs are completely depleted (Dix et al, 2018), while RAs are maintained to enable effective mitosis and daughter cell respreading (Lock et al, 2018; Zaidel-Bar, 2018; Li and Burridge, 2019). This dramatic yet naturally occurring perturbation of the canonical AC–RA/plaque equilibrium now provides an instructive setting in which to interrogate mechanisms controlling this balance, though it remains unclear if the RAs that attach mitotic cells are identical to clathrin plaques or maintain the same molecular composition as during interphase.…”
Section: Why Are Ra/plaques Used At Mitosis?mentioning
confidence: 99%
“…All of the 5 top degree mRNAs were overexpressed in ccRCC. CDK1 is essential for the eukaryotic cell cycle by regulating the onset of mitosis and the centrosome cycle (30). A previous study indicated that CDK1 expression was highly associated with the prognosis of patients with RCC (31).…”
Section: Discussionmentioning
confidence: 99%